Physical Activity, Food Consumption, and Breakfast among Normal and Overweight Elementary School Children in Bogor during Covid-19 Pandemic - Putri, Dini Rizkiani; Dwiriani, Cesilia Meti; Briawan, Dodik (Jurnal Gizi dan Pangan, 2021)
The objective of this study was to analyze differences in physical activity, quality of food consumption and breakfast between elementary school children with normal and overweight nutritional status in Bogor City of Indonesia during the Covid-19 pandemic. This was a cross sectional study carried out from September 2020 to January 2021 in nine elementary schools in Bogor City. This research was conducted when school from home had been running for about six months. Survey was conducted using a structured questionnaire filled by the subject's parents via google form and Microsoft word and then interviewing via whatsapp. Physical activity measured using the Physical Activity Level (PAL) method and food consumption quality using the Individual Dietary Diversity Score (IDDS). Breakfast quality based on the intake and contribution of energy and protein at breakfast. Result showed that 70% of male and 30% of female subjects were classified as overweight. There was a significant difference in the PAL value between subjects with normal weight and overweight (2.02 vs 1.63, p<0.05). There were no significant differences in IDDS of normal weight and overweight students in both weekday and weekend (p>0.05). However, IDDS scores of students with normal nutritional status was higher (7.08 and 8.60) compared to (6.80 and 6.78) in overweight students during the weekday and weekend respectively. In contrast, the energy and protein intake consumed during breakfast for overweight students was higher (617 kcal/day and 21 g/day) than students with normal nutritional status (477 kcal/day and 18.2 g/day) (p<0.05). This study has shown the importance to educate parents of overweight subjects to increase their children's physical activity as the students with normal nutrition status do as well as to provide breakfast with a more diverse menu